2014
DOI: 10.3389/fnagi.2014.00214
|View full text |Cite
|
Sign up to set email alerts
|

Altered protein phosphatase 2A methylation and Tau phosphorylation in the young and aged brain of methylenetetrahydrofolate reductase (MTHFR) deficient mice

Abstract: Common functional polymorphisms in the methylenetetrahydrofolate reductase (MTHFR) gene, a key enzyme in folate and homocysteine metabolism, influence risk for a variety of complex disorders, including developmental, vascular, and neurological diseases. MTHFR deficiency is associated with elevation of homocysteine levels and alterations in the methylation cycle. Here, using young and aged Mthfr knockout mouse models, we show that mild MTHFR deficiency can lead to brain-region specific impairment of the methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…MTHFR is the rate-limiting enzyme for the conversion of folate to active 5MeTHF, hence knockout mice have elevated Hcy and altered methylation potential (see Figure 1). In young and aged Mthfr knockout mouse models, it was demonstrated that mild MTHFR deficiency decreases methylation of PP2A in a region-specific manner (Sontag et al, 2014). The effects were exacerbated by folate deficiency which significantly decreased methylated PP2A levels associated with increased P-tau.…”
Section: Tau Phosphorylationmentioning
confidence: 99%
See 4 more Smart Citations
“…MTHFR is the rate-limiting enzyme for the conversion of folate to active 5MeTHF, hence knockout mice have elevated Hcy and altered methylation potential (see Figure 1). In young and aged Mthfr knockout mouse models, it was demonstrated that mild MTHFR deficiency decreases methylation of PP2A in a region-specific manner (Sontag et al, 2014). The effects were exacerbated by folate deficiency which significantly decreased methylated PP2A levels associated with increased P-tau.…”
Section: Tau Phosphorylationmentioning
confidence: 99%
“…Conversely, inducing high plasma Hcy levels (vs. mild as with (Sontag et al, 2014)), caused tau hyperphosphorylation at multiple sites, inhibition of PP2A activity and alterations in the PP2Ac subunit, with methylesterase activation leading to demethylation of PP2Ac (Zhang et al, 2008). Upon administration of folate and B12 the HHcy was reversed preventing tau hyperphosphorylation, inactivation of PP2A and modified activity of PP2Ac but no change was exhibited in GSK3.…”
Section: Tau Phosphorylationmentioning
confidence: 99%
See 3 more Smart Citations